The Study of Symptom-Management's Self-Efficacy in Breast Cancer Survivors Undergoing Chemotherapy - Fatemeh Moghaddam Tabrizi; Saeedeh Alizadeh; Samira Barjasteh (Hamadan University of Medical Sciences, 2018)
Introduction: Self-efficacy emphasizes on skills and abilities to carry out successful worthy performance. The aim of this study was to evaluate the symptom-management's self-efficacy associated with chemotherapy and its related factors in women referred to academic centers of Urmia in 2016. Methods: This study was a descriptive-analytical cross-sectional study conducted on 150 patients with breast cancer referred to academic centers of Urmia in 2016 and sampling method was convenience. The collecting data instrument was the symptom-management's self-efficacy scale-breast cancer (SMSES-BC) questionnaire with three subscales including acquiring problem-solving, managing chemotherapy-related symptoms and managing emotional and interpersonal disorders. The data was analyzed using SPSS20.  Results: Most of the patients were in the age range of 41-49. The Lowest scores were in the area of ​​emotional and interpersonal disorders and the highest scores were in the area of ​​ managing chemotherapy-related symptoms. The mean score of self-efficacy chemotherapy-related symptoms was 167.96±25.40. There was a significant relationship between age (P=0.024), economic status (P=0.006), education, marital status, and life status (P=0.001) and  self-efficacy chemotherapy-related symptoms. Conclusion: Interventional efforts to promote the function of symptom management self-efficacy, especially managing emotional and interpersonal disturbance in these patients are important and necessary.